Socioeconomic status and older adult's experiences of weight loss: a qualitative secondary analysis. - Anna Newton-Clarke; Miriam J Johnson; Ugochinyere Nwulu; Fliss E M Murtagh; Alex F Bullock (PLoS ONE)
Objectives Unintentional weight loss in older adults is common, with 15-20% of those aged >65 having clinically significant weight loss, associated with increased mortality and morbidity. People with socioeconomic disadvantage are more likely to be overweight but also to become frailer in older age. We explore if socioeconomic status impacts upon patients' experience of unplanned weight loss. Methods Qualitative secondary analysis of 23 semi-structured interviews with older adults from two prior studies i), those at risk of frailty ii) those with cancer. Reflexive thematic analysis was conducted, using the lens of the Nutrition Equity Framework, on anonymised transcripts with formation of themes and subthemes, with relationships between themes investigated. Results Mean age 73 years, range 65-87; 34% male, Index of Multiple Deprivation Quintiles IMD 1 (n=9), IMD 2 (n=4), IMD 3 (n=3), IMD 4 (n=6), IMD 5 (n=1). Three major themes were identified. 1. 'Healthcare Systems'; interactions with either public health or individual healthcare systems influence patient experiences of weight loss. 2. 'Personal Factors'; that influence a patient's view of weight loss and the likelihood of weight loss prompting help-seeking behaviour 3. 'Can I Change?'; patients' perspectives of their ability to implement change. Factors in each of the themes were understood through motivating (reinforcing) and demotivating (balancing) factors. Conclusions This study demonstrates that there is structural and individual inequity in individual views, identification, and clinical management of weight loss. The consequences of this disproportionately affect the most deprived, further confounding the inequalities that already exist.